Integrative analysis by targeted metabolomics revealed the regulatory function of donkey oil on skin metabolites - Li, Min; Sun, Jinni; Liu, Guangyuan; Chen, Zhijie; Wu, Tao; Tie, Hang; Wang, Cong (Frontiers in Medicine, 2025)
BackgroundDonkey oil, an edible oil rich in unsaturated fatty acids and vitamin E, has the potential to become a multifunctional ingredient for skincare. However, its molecular mechanisms in maintaining skin health remain unknown.MethodsIn this study, 64 volunteers with either healthy or inflammatory skin were divided into two groups and applied donkey oil for 28 days. Then, we measured the targeted metabolites including 65 kinds of organic acids, 94 kinds of amino acids, and 48 kinds of free fatty acids and their derivates in the skin by comparative metabolomics analysis of two groups to assess changes before and after application.ResultsWe found differential levels of seven (three upregulated and four downregulated) organic acids in the healthy skin group, six (two upregulated and four downregulated) organic acids in the inflammatory skin group, and one shared organic acid (4-hydroxyphenylacetic acid) in response to donkey oil application after 28 days. Regarding amino acids and their derivatives and free fatty acids, 10 (1 upregulated and 9 downregulated) amino acids and derivatives were found in the healthy skin group, while 7 (2 upregulated and 5 downregulated) were found in the inflammatory skin group. Additionally, three shared amino acids and their derivatives (5-hydroxytryptamine, tryptophan, and 5-aminovaleric acid) were found. For free fatty acids, 10 (8 upregulated and 2 downregulated) were regulated in the healthy skin group, and 7 (1 upregulated and 6 downregulated) were regulated in the inflammatory skin group. Furthermore, six shared free fatty acids were regulated by donkey oil.ConclusionBy metabolite functional annotation, donkey oil may influence the levels of several metabolites, including 4-hydroxyphenylacetic acid, 5-hydroxytryptamine, tryptophan, 5-aminovaleric acid, decanoic acid, octanoic acid, cis-11,14,17-eicosatrienoic acid, myristic acid, tridecanoic acid, and pentadecanoic acid. These metabolites are mainly enriched in aromatic amino acid metabolism and fatty acid biosynthesis metabolism to facilitate the maintenance of skin homeostasis.